PROPHYLACTIC ADMINISTRATION OF DOXYCYCLINE REDUCES CENTRAL VENOUS CATHETER INFECTIONS IN PATIENTS UNDERGOING HEMATOPOIETIC CELL TRANSPLANTATION - Mohamed Kharfan-Dabaja; Mohamed Baydoun; Zaher Otrock; Samar Okaily; Rita Nehme; Racha Abu-Chahine; Ali Hamdan; Samar Noureddine; Souha Kanj; Zeina Kanafani; Ali Bazarbachi (Mediterranean Journal of Hematology and Infectious Diseases)
Hematopoietic stem cells are usually transfused through a central venous catheter (CVC), which also facilitates administration of medications and intravenous fluids. We had observed high rate of catheter-related blood-stream infection (CR-BSI) at our Bone Marrow Transplantation (BMT) unit despite prescribing fluoroquinolones for anti-bacterial prophylaxis. Accordingly, we implemented prophylactic use of a relatively inexpensive broad spectrum antibiotic, namely doxycycline to address this problem. We wanted to investigate whether doxycycline prophylaxis reduces CR-BSI rate. Data was collected retrospectively on 54 consecutive patients, 26 of whom received doxycycline (doxycycline group), and we compared their outcomes to a previous cohort of 28 patients who did not receive doxycycline (comparison group). The groups were comparable in regards to age, gender, hematopoietic cell transplant type, and primary diagnosis. No CVC infection (0%) was observed in the doxycycline group, while 5 infection episodes (18.5%) occurred in 4 patients in the comparison group (p<0.001). Episodes of CR-BSI were due to: Escherichia-coli (EC)=1, coagulase-negative Staphylococcus-spp (CNSS)=2, both EC & CNSS=1. Our results demonstrate that CR-BSI was reduced significantly after introducing doxycycline. This finding suggests a beneficial role for systemic use of doxycycline prophylaxis to prevent CR-BSI in adult BMT patients. Nevertheless, a randomized controlled study is warranted to confirm these findings.